Tourist Market of Visiting Friends and Relatives - I Dewa Gde Satrya (Ilomata International Journal of Social Science, 2023)
Visiting friends and relatives who live in different cities or countries is a trigger for travel. This research aims to describe the travel experiences of informants from Bali when visiting friends and relatives in East Java. Many activities and tourist destinations that can be visited when visiting friends and relatives in different cities. However, due to limited time, energy and costs, priority is needed in determining the itinerary when visiting friends and relatives so as to optimize the benefits obtained. The formulation of the problem in this research is how the travel experiences of informants from Bali when visiting friends and relatives in East Java? The novelty in this research lies in the qualitative way of determining the itinerary of visiting friends and relatives in order to get optimal benefits. This research was conducted with a qualitative approach. Primary data was obtained through interviews and observations of sources from family travelers from Bali who visited friends and relatives in East Java. Secondary data obtained from relevant previous research. Visiting friends and relatives itinerary based on the main goal or priority of the friends and relatives you want to visit. Apart from the city of Surabaya, family travelers from Bali also want to travel to the city of Batu. However, because the top priority is visiting Surabaya, traveling to Batu is done in half a day, and choosing priority tourist destinations.